2011
DOI: 10.1038/sj.bjc.6606083
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ZAG production by subcutaneous adipose tissue is linked to weight loss in gastrointestinal cancer patients

Abstract: Background:Profound loss of adipose tissue is a hallmark of cancer cachexia. Zinc-α2-glycoprotein (ZAG), a recently identified adipokine, is suggested as a candidate in lipid catabolism.Methods:In the first study, eight weight-stable and 17 cachectic cancer patients (weight loss ⩾5% in previous 6 months) were recruited. Zinc-α2-glycoprotein mRNA and protein expression were assessed in subcutaneous adipose tissue (SAT), subcutaneous adipose tissue morphology was examined and serum ZAG concentrations were quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 40 publications
5
106
0
7
Order By: Relevance
“…Similar to the loss in muscle mass, the most rapid loss of fat in patients with colorectal liver metastases occurs within 2 mo of death (19). In addition to the loss of fat mass, patients with cancer cachexia experience adipose tissue remodeling characterized by the shrinkage of adipocytes and an increase in interstitial spaces (21). Similar to humans, MoCR mice had a loss of fat mass, reduced adipocyte size, and an increased proportion of nonadipocyte tissue.…”
Section: R861mentioning
confidence: 83%
“…Similar to the loss in muscle mass, the most rapid loss of fat in patients with colorectal liver metastases occurs within 2 mo of death (19). In addition to the loss of fat mass, patients with cancer cachexia experience adipose tissue remodeling characterized by the shrinkage of adipocytes and an increase in interstitial spaces (21). Similar to humans, MoCR mice had a loss of fat mass, reduced adipocyte size, and an increased proportion of nonadipocyte tissue.…”
Section: R861mentioning
confidence: 83%
“…However, in agreement with Raiszadeh et al, the present data do not support the notion that IL-6 is present in sweat in detectable levels and we suggest that measurement of IL-6 in sweat is not a valid or reliable measurement of systemic IL-6. Moreover, of 180 proteins identified in sweat, only albumin, zinc α2 glycoprotein, gelsolin, apolipoprotein D and clusterin 1 were present in both sweat and plasma (Raiszadeh et al 2012), indicating that future work aimed at using sweat as a potential vehicle for biomarkers or disease should focus on these proteins, as they have already been linked to a number of diseases and pathological conditions (Ceperuelo-Mallafré et al 2009;Dubois et al 2010;Hassan et al 2008;Mracek et al 2011;Rydén et al 2012;Yang et al 2013). …”
Section: )mentioning
confidence: 99%
“…In cachectic cancer patients ZAG mRNA showed a negative correlation with body mass index (BMI), but a positive correlation with weight loss and serum glycerol levels (4). In contrast ZAG mRNA levels in WAT have been shown to be down regulated in obesity and correlated negatively with fat mass, BMI, plasma insulin and leptin (5).…”
mentioning
confidence: 99%
“…Later studies showed that ZAG was also produced in normal tissues including liver, brown adipose tissue (BAT) and white adipose tissue (WAT) (3), so that ZAG can be classified as an adipokine. Moreover, in both cachectic mice (3) and humans (4) expression of ZAG mRNA in WAT was found to be increased 10-fold (3) and 2.7-fold (4) respectively.…”
mentioning
confidence: 99%